Revitalizing Local Wisdom through Fictional Texts: Enhancing Reading Comprehension in Indonesian Primary Classrooms - Sukida, Sukida; Sulfasyah, Sulfasyah; Tarman, Tarman (IAIN Manado, 2025)
Reading comprehension is a foundational skill in early education, yet many Indonesian primary students struggle with it due to instructional materials that are culturally distant and pedagogically static. This study aims to develop a fictional reading module grounded in kearifan lokal (local wisdom) from Bone, South Sulawesi, using the Four-D development model: Define, Design, Develop, and Disseminate. The module incorporates the folklore of Goa Mampu, embedding moral values and regional identity within narrative texts designed for fourth-grade students. Validation involved expert reviews and field testing in a local elementary school. Results showed the materials achieved high validity (mean expert score: 3.8/4.0), strong effectiveness (mean post-test score: 87%), and high practicality based on teacher and student responses. Students demonstrated marked improvements in literal, inferential, and critical reading comprehension. Beyond academic gains, the module strengthened learners' cultural awareness and engagement. This research underscores the pedagogical value of integrating localized, story-based content into national curricula, particularly in multicultural education systems. It also highlights the role of culturally responsive materials in promoting equitable literacy outcomes. The findings contribute to a growing movement for curriculum contextualization in educational contexts of the Global South.